The Analysis of Opinion Evolution and Control Based on the Prisoner's Dilemma Game in Social Networks. (30th January 2021) - Li, Xianyong; Zhu, Jian; Du, Yajun; Zhang, Qian
Abstract : In a social network, a user is greatly influenced by their neighbors' opinions, and the user's opinion updating can be regarded as the prisoner's dilemma game. In view of such considerations, this paper proposes an opinion evolution and control model based on the prisoner's dilemma game and gives the corresponding opinion evolution and control algorithm. Under different initial positive opinion proportions, different opinion control levels, and the same control threshold value and under different initial positive opinion proportions, different opinion control levels, and different opinion control threshold values in a scale-free network, the experiments illustrate the opinion evolution trends and control strategies according to the measures of changing the opinion control levels and opinion control threshold values for network regulators. The experiments show that the lower the initial positive opinion proportion is and the smaller (resp., larger) the control opinion threshold value chosen by the network regulators is, the lower (resp., higher) the opinion control level is; the larger the initial positive opinion proportion is and the larger the control opinion threshold value chosen by the network regulators is, the lower the opinion control level is.